DETERMINING THE MUJTAHID MADHHAB: THE CONTRIBUTION OF ABDUL WAHHAB AL-MALIKI'S THOUGHTS ON ISLAMIC JURISPRUDENCE - Graiguer Abdelmounaim; A. Amir Firmansyah (UIN Kiai Haji Achmad Siddiq Jember, 2023)
This research attempts to improve the procedures (conditions) for forming a mujtahid in Islamic Jurisprudence, who is worthy of being called a mujtahid in deciding issues, Commands, Prohibitions, and the permissibility of Allah. The point of forming a mujtahid is often discussed by fundamentalists and people who have difficulty